METODE TAFSIR TAHLILI; SOLUSI PROBLEMATIKA PADA PENDIDIKAN KELUARGA ISLAM - Maskuri (Penerbit CV Tentrem Karya Nusa, 2018)
Method is one of the most important means to achieve the purpose set. From here, wecan know the commentary on QS. Lukman: 15 it helps the problematic that occurs when thedifference of opinion between a child and the parents, where the parent asks to stay away fromGod while the child refuses, and that does not mean the child is ungodly and vice versa, because theabove verse has been supported by the existence of other verses and hadiths that reinforce theexistence of such dissidents. To the end, where a child is different from belief, the child demandsnot to defend him, the Prohibition hates the parents as mentioned above. Therefore, it is supportedby the letters and meanings contained in QS. Lukman: 15, there is a keyword is ma'ruf in this case,ma'ruf is a word that shows the child's ethics to his parents.Key Words: Tahlili Method, Problematic, Islamic Family Education